Performance analysis and testing of personal influence algorithm in online social networks - Yong QUAN; Yan JIA; Liang ZHANG; Zheng ZHU; Bin ZHOU; Binxing FANG (Tongxin xuebao)
Social influence is the key factor to drive information propagation in online social networks and can be modeled and analyzed with social networking data.As a kind of classical personal influence algorithm,two parallel implementation versions of a PageRank based method were introduced.Furthermore,extensive experiments were conducted on a large-scale real dataset to test the performance of these parallel methods in a distributed environment.The results demonstrate that the computational efficiency of the personal influence algorithm can be improved significantly in massive data sets by virtue of existing big data processing framework,and provide an empirical reference for the future research and optimization of the algorithm as well.